SUITSIDAL XULQ XAVFINI YUZAGA KELISHIDA DEMOGRAFIK VA GENDER MASALALARI - Qarshiboeva, G.A. (SCIENCE and SOCIETY, 2024)
The article highlights the risk of suicidal behavior taking into account demographic and gender characteristics, and low self-esteem, alcohol and drug use can also affect the risk of suicidal behavior in them. It has been established that their suicidal behavior arises on the basis of abnormality, the inability to realistically evaluate events, and dissatisfaction with oneself.
Keywords: suicidal behavior; risk manifestations; alcohol and drugs; exposure. abnormality; events; realistic assessment; dissatisfaction with oneself